SHMT2 Overexpression Predicts Poor Prognosis in Intrahepatic Cholangiocarcinoma - Shanglei Ning; Siquan Ma; Abdul Qahar Saleh; Lingyu Guo; Zixiao Zhao; Yuxin Chen (Gastroenterology Research and Practice)
Background and Objective. Serine hydroxymethyltransferase 2 (SHMT2) functions as a key enzyme in serine/glycine biosynthesis and one-carbon metabolism. Recent studies have shown that SHMT2 participated in tumor growth and progression in a variety of cancer types. The objective of the present study is to explore the expression of SHMT2 and evaluate its prognostic value in patients with intrahepatic cholangiocarcinoma (iCCA). Patients and Methods. We retrospectively investigated the expression of SHMT2 in 100 primary iCCA samples through immunohistochemical (IHC) staining on a tissue array. Results. High SHMT2 expression was found in 52 of the 100 specimens. The results indicated that SHMT2 level was upregulated compared to adjacent nontumor intrahepatic bile duct tissue. Furthermore, SHMT2 level was closely associated with tumor T stage (P=0.017) and tumor TNM stage (P=0.041) in patients with iCCA, but not with age, gender, tumor size, tumor number, pathological grade, vascular invasion, or N stage. Moreover, Kaplan-Meier analysis suggested that patients with lower SHMT2 level have longer survival rate than those with high expression (45.8 vs 23.1%, P=0.030). Additionally, the multivariate analysis model indicated SHMT2 is an independent adverse prognosticator in iCCA. Conclusion. High SHMT2 level was correlated with poorer overall survival in patients with iCCA. SHMT2 was proved to be a powerful and independent prognostic factor and a potential therapeutic target for patients with iCCA.